METHODOLOGICAL ASPECTS OF ONLINE FORMS OF TEACHING - Haskova, Alena; Gadusova, Zdenka; Havettova, Romana (Journal of Education Culture and Society, 2021)
Aim. The paper presents results of a questionnaire survey which aim was to find out English learners´ preferences of different platforms and applications to be used for home schooling.   Concept. Key attention of the authors is paid to the issue of the transition of face-to-face forms of education to online platforms, caused by school closures due to the coronavirus pandemic in 2020. At first, they deal with the use of digital technologies in teaching in general. They analyse how digital didactic means were used prior to the pandemic situation and they present research results related to differences among the ways of the use of these means within different subjects teaching (natural science subjects, technically oriented subjects, languages, social science subjects, artwork subjects). Consequently, the authors deal with the methodological aspects of the use of online forms in foreign language teaching.   Methodology. To find answer to such questions as which educational form, school education or home schooling, is more preferred by English learners, what are the strengths and weaknesses of home schooling, which foreign language skills are being practiced via online Zoom lessons,  which foreign language skills are being practiced via worksheets, or which mobile applications are used to enlarge students` vocabulary range, a questionnaire survey was carried out. Respondents of the survey were English learners, secondary vocational school students,,aged from 16 to 20 year-olds.   Results and conclusions. Based on the analysis of the data recorded from the learners` responses to the particular questionnaire items as the most significant three weaknesses of the home schooling were identified technical problems, more homework and lack of social contacts, while as the main strengths were found out home comfort, sufficient sleeping time and less dense timetable.